Effect of Water on Removal Efficiency of Sulfur-Containing Compounds from Crude Oil Models Using Ionic Liquids - NURUL NADIAH BINTI NOOR AZLI, NURUL NADIAH (Universiti Teknologi Petronas, 2009)
The objective of the project is to determine the effect of water on sulfur-compounds removal efficiency of ionic liquids from crude oil models using ionic liquids. Six types of Ionic Liquids (ILs) were employed: - Bmim OcSO4 (1-butyl-3-methylimidazolium octylsulfate) - Bmim OTf (1-butyl-3-methylimidazolium trifluoromethanesulfonate) - Hmim NTf2 (1-hexyl-3-methylimidazolium bis {(trifluoromethyl) sulfonyl} amide ) - Mmim DMP (1-methyl-3-methylimidazolium dimethylphosphate) - Emim DEP (1-ethyl-3-methylimidazolium diethyl phosphate) - Bmim DBP (1-butyl-3-methylimidazolium-dibutyl-phosphate) All ILs were exposed to the surroundings for four hours, and the water content of each IL were monitored as a fraction of time using Karl-Fisher Titration. The sulfur removal efficiency was also determined. After four hours of exposure, the water content for all the ionic liquids increased by 36.2%, 43.5%, 211.7%, 396.6%, 487.1%, and 1192.9% for Bmim OcSO4, Bmim DBP, Mmim DMP, Emim DEP, Hmim NTf2 and Bmim OTf. After four hours of exposure, all ILs showed that the sulfur removal efficiency decreased by 25.5%, 33.4%, 1.6%, 10.9%, 5.4% and 3.2% for Emim DEP, Hmim NTf2, Bmim OTf, Bmim OcSO4, Bmim DBP and Mmim DMP. Bmim OTf although has the highest capacity to absorb water, it displayed the lowest sensitivity to the effect of water on sulfur of water on sulfur removal efficiency. Thus, further work can be done to test on the capability of Bmim Otf to remove sulfur with the presence of water.